Ecological similarity promotes coexistence between taxonomically related dung beetles species - Beiroz, Wallace; Vieira, Letícia; Louzada, Julio (Acta oecologica (Montrouge), 2019)
Theoretically, a pair of species might coexist if they converge to an optimal phenotype and are not able of excluding each other, even under niche overlap conditions. We empirically evaluated this hypothesis analyzing the niche overlap for two coexisting dung beetles species in Brazilian coastal sand dune forest. The species exhibit a high degree of niche overlap, regarding temporal activity, food, and habitat use, exhibiting only subtle differences in the number of individuals sampled in distinct foraging times and habitats. Opposite to classically expected, species’ body mass converged in coexistence condition when contrasted to areas where each species is numerically dominant. Our findings show that two similar species can coexist without divergence in their niche axes if they are above the threshold of similarity, suggesting higher levels of intraspecific than interspecific competition. This competitive scenario is evidenced by body's mass reduction of both species when coexisting. •We analyzed the niche partitioning of two taxonomically related dung beetles in Brazilian Coastal ecosystems.•We discovered that this two similar species can coexist without divergence in their niche axes.•Both species converged to a similar phenotype resulting in higher levels of intraspecific than interspecific competition.